2016
DOI: 10.1515/bjmg-2016-0008
|View full text |Cite
|
Sign up to set email alerts
|

PECAM-1gene polymorphism (rs668) and subclinical markers of carotid atherosclerosis in patients with type 2 diabetes mellitus

Abstract: The platelet endothelial cell adhesion molecule 1 (PECAM-1) plays an important role in many inflammatory processes, including the development of atherosclerosis. Polymorphism rs668 of the PECAM-1 gene (373C/G) is functional, and it was reported to be associated with increased serum levels of PECAM-1. We investigated the association between the rs668 polymorphism of PECAM-1 and subclinical markers of carotid atherosclerosis in subjects with type 2 diabetes mellitus (T2DM). Five hundred and ninety-five T2DM subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The PECAM-1 is an adhesion molecule that plays a vital role in vascular biology. Previous studies reported that PECAM-1 polymorphisms have been associated with coronary artery stenosis or atherosclerosis [ 23 25 ]. Three common polymorphisms (Leu125Val, Asn563Ser, and Gly670Arg) located on the PECAM-1 gene have been verified to be in association with these diseases [ 8 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PECAM-1 is an adhesion molecule that plays a vital role in vascular biology. Previous studies reported that PECAM-1 polymorphisms have been associated with coronary artery stenosis or atherosclerosis [ 23 25 ]. Three common polymorphisms (Leu125Val, Asn563Ser, and Gly670Arg) located on the PECAM-1 gene have been verified to be in association with these diseases [ 8 , 24 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of T2DM is not well understood, but it is now generally believed that this disease may be related to the genetic, personal and environmental factors. Among these, genetic polymorphisms in nuclear genes have been reported to be associated with T2DM [ 2 ]. However, the maternally inherited pattern of T2DM may also be frequent [ 3 ], highlighting the importance of mitochondrial disfunction in T2DM.…”
Section: Introductionmentioning
confidence: 99%